DISPLAYING THE PRINCIPLE OF EQUITY OF ECOLOGICAL COMPONENT: THE THEORETICAL AND LEGAL ASPECTS OF SUSTAINABLE DEVELOPMENT - N.O. Herasymenko (Економіка та право)
The article was analyzed international and national regulations on sustainable development and environmental protection in order to identify signs of the principle of fairness in legal support of the ecological component of sustainable development in order to achieve the global goal of protecting and improving the environment for the benefit of present and future generations. It was found that the final document of the United Nations summit on the adoption of the development agenda for the period beyond 2015: The transformation of our world: the Agenda for Sustainable Development for the period up to 2030, is the determining factor in shaping the current legal framework for sustainable development and the Association Agreement between Ukraine, on the one hand, and the European Union, the European Atomic Energy Community and their member states, on the other. The positive tendency of transformation of the domestic legislation on the issues of integration of environmental policy into other sectoral policies has been revealed. Established the existence of the principle of equity, with a distinction between the principles of equalizing and reciprocal equity, in the legal provision of the environmental component of Ukraine’s sustainable development. At the same time, the law-making and law enforcement activities in terms of implementing the principle of «paid equity» need improvement. It is noted that the issue of ensuring environmental safety plays an important role in the context of sustainable development, and therefore should be embodied in the fundamental national interests of Ukraine, provided for in the Law of Ukraine «On National Security of Ukraine». The activation of the processes of shaping Ukraine’s climate policy in the framework of achieving one of the global goals of sustainable development regarding taking urgent measures to combat climate change and its consequences is noted positively.